Comment approfondir la coopération entre rive nord et rive sud de la Méditerranée : Un renouveau économique tenant compte des effets de la rente sur le Sud de la Méditerranée - Hartmut Elsenhans (L’Année du Maghreb)
Genuine Euro-Mediterranean cooperation cannot be achieved without opening the Arab world to development via industrialization. Without an agricultural surplus, the Arab world cannot follow the East Asian strategy of massive devaluations to make manufactured exports competitive. The EU could address this lack of agricultural surplus by assigning its own agricultural surplus to the economic transformation of the Arab world, in this way promoting social and political stability on the basis of the comparative advantage that will appear when the Arab world has managed its industrialization. To implement such a strategy, we must break with the simplistic models which oppose market, planning, production and autocentric development.